Penerapan Pendekatan SDGs dalam Penguatan Literasi dan Numerasi untuk Guru PAUD di Kecamatan Stabat, Kabupaten Langkat - Frisnoiry, Suci; Srinahyanti, Srinahyanti; Surya, Edi; Khairani, Nerli; Frimaulia, Sara; Siregar, Tiur Malasari; Elfitra, Elfitra (Universitas Muhammadiyah Prof. DR. Hamka (UHAMKA Press), 2026)
Background: Literacy and numeracy are fundamental competencies in fostering critical thinking skills in early childhood; however, early childhood education teachers in Stabat District, Langkat Regency, face limitations in integrating literacy and numeracy instruction with the values of the Sustainable Development Goals (SDGs). Objective: This community service program aimed to enhance teachers’ competencies in implementing SDGs-based literacy and numeracy learning in a contextual and meaningful manner. Methods: The program employed a Participatory Action Research (PAR) approach over three months, comprising stages of socialization, training, and workshops; implementation of educational technology; mentoring; and evaluation. Data were collected using pre-test and post-test instruments, classroom observations, and teacher reflections, and were analyzed descriptively by comparing pre- and post-intervention conditions. Results: The findings indicate a significant improvement in teachers’ average understanding of literacy (from 56.4 to 82.1), numeracy (from 53.8 to 80.6), and the integration of the SDGs (from 48.2 to 79.3). In addition, one-way instructional practices decreased from 72.5% to 20.0%, while interactive learning increased to 80.0%, and the use of innovative learning media reached 85.0%. Conclusion: The SDGs-based literacy and numeracy approach effectively strengthened teachers’ pedagogical competencies and promoted more interactive, contextual, and sustainable early childhood learning practices.